DESIGN, FABRICATION AND PERFORMANCE EVALUATION OF A PORTABLE HAND-HELD REFRACTOMETER (Nigerian Journal of Technology, 2018)
Refractometer is a simple optical instrument that measures the amount of light refracted in a liquid. It measures on a "Brix" scale and the Brix level determines the flavor and quality of fruits and vegetables. The fabricated refractometer has built-in temperature compensations for Brix measurements and it is only valid for fruit juices solutions   The refractometer is equipped with a thermometer and there is a means of circulating water through the refractometer to maintain a given temperature The designed refractometer consists of a light source, filtered to a single wavelength, which is directed towards the prism-sample interface by a converging lens. This creates a range of incidence angles, some of which will be completely reflected. A Charge-coupled Device (CCD) sensor precisely measures the intensity of the reflected light and determines the exact angle at which light begins to be completely reflected.  The fabricated refractomter consists of six main parts which include focus adjustment, calibration screw, daylight plate, eye piece, rubber grip and main prism assembly. Actual tests were conducted using samples of orange, pineapple and cashew juices at certain levels of pH values. The average percentage Brix values of orange, cashew and pineapple juices are 7.88%, 10.84% and 6.91% respectively.  It was observed that cashew juice has highest percentage Brix followed by orange and pineapple juices. This implies that cashew juice can deteriorate faster than the other two juices. The analysis of variance (ANOVA) for the effect of temperature and pH used for the experiment show that F-calculated (4.248) is greater than F-table (3.35) at 5% probability level; therefore, the pH of fruit juice has an effect on its brix value. It appears that the rate of pH or temperature sensitivity of the fabricated refractometer used could not be the actual or maximum rate for the experiment http://dx.doi.org/10.4314/njt.v37i2.33